Strata Movement and Fracture Propagation Characteristics due to Sequential Extraction of Multiseam Longwall Panels - Xiangyang Zhang; Behrooz Ghabraie; Gang Ren; Min Tu (Advances in Civil Engineering)
Multiseam longwall mining-induced strata deformation and fracture propagation patterns are different from those of single-seam mining. This difference is due to interaction of the caved zones as a result of longwall mining activity at different coal seams, which severely impacts formation of subsidence and permeability of the strata after multiseam mining. Understanding this phenomenon is of great importance in order to predict the multiseam subsidence reliably, evaluate the risk of water inrush and take suitable preventive measures, and determine suitable locations for placing gas drainage boreholes. In this study, scaled physical modelling techniques are utilised to investigate strata deformation, fracture propagation characteristics, and vertical subsidence above multiseam longwall panels. The results show that magnitude of the incremental multiseam subsidence increases significantly after multiseam extraction in comparison with single-seam mining. This increase occurs to different extent depending on the multiseam mining configuration. In addition, interstrata fractures above the abutment areas of the overlapping panels propagate further towards the ground surface in multiseam extractions compared with single-seam extractions. These fractures increase the risk of water inrush in presence of underground/surface water and create highly permeable areas suitable for placing gas drainage boreholes.